ความเป็นพิษต่อเซลล์ ฤทธิ์ต้านการอักเสบและต้านอนุมูลอิสระของตำรับยาห้ารากที่สกัดด้วยน้ำ - กวานเหียน, วิยดา; บรรลือพืช, กิ่งกาญจน์ (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2018)
Ya-Ha-Rak (YHR) as a Thai traditional herb formula. YHR has been widely used in as traditional antipyretics drug. Its ingredients consist of five types of herbal roots. The traditional using of YHR is boiling which is water extraction. In this study, we investigated the effect of water extracted-YHR on anti-inflammatory effect on RAW 264.7 macrophages cells which stimulated by lipopolysaccharide (LPS). In addition, anti-oxidation efficacies were determined the scavenging DPPH and ABTS radical activity. The cytotoxic concentration 50 (CC50) of water extracted-YHR was 44.32+3.25 µg/ml. Anti-inflammatory efficacy by nitric oxide releasing inhibition was shown as inhibitory concentration 50 (IC50) 16.56 µg/ml. The anti-oxidation efficacy was determined the DPPH and ABTS radical scavenging. The scavenging concentration 50 (SC50) was 120.17+0.07 and 73.27+0.08 µg/ml, respectively. The results can confirm the anti-inflammatory and anti-oxidant efficacies of water extracted YHR.